2018
DOI: 10.3847/2041-8213/aab103
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Limits of AGN Feedback: Black Holes and the Star Formation Histories of Low-mass Galaxies

Abstract: Energy feedback, either from active galactic nuclei (AGN) or from supernovae, is required to understand galaxy formation within a Λ-Cold Dark Matter cosmology. We study a sample of 127 low-mass galaxies, comparing their stellar populations properties to the mass of the central supermassive black hole, in order to investigate the effect of AGN feedback. We find a loose coupling between star formation history and black hole mass, which seems to suggest that AGN activity does not dominate baryonic cooling in low-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 51 publications
4
30
0
Order By: Relevance
“…There is now growing evidence suggesting that the baryonic properties of massive galaxies, namely their ages, star formation rates, and chemical composition, are tightly coupled to the masses of their central super-massive black holes , 2018bMartín-Navarro & Mezcua 2018;Terrazas et al 2016Terrazas et al , 2017. The observed relation between black holes and coronal gas temperature described in § 2 provides further observational evidence for a scenario where the star formation in massive galaxies is regulated by the energetic input from the central black hole.…”
Section: Discussionmentioning
confidence: 87%
“…There is now growing evidence suggesting that the baryonic properties of massive galaxies, namely their ages, star formation rates, and chemical composition, are tightly coupled to the masses of their central super-massive black holes , 2018bMartín-Navarro & Mezcua 2018;Terrazas et al 2016Terrazas et al , 2017. The observed relation between black holes and coronal gas temperature described in § 2 provides further observational evidence for a scenario where the star formation in massive galaxies is regulated by the energetic input from the central black hole.…”
Section: Discussionmentioning
confidence: 87%
“…For this reason, BHs with M • 10 5 M fail to reach the mass dictated by their velocity dispersion and become under-massive. Previous observations (e.g., Martín-Navarro & Mezcua 2018) and simulations (e.g., Anglés-Alcázar et al 2017;Habouzit et al 2017) already suggested that feedback is driven by BH activity for M • 10 5 M and by supernova-driven winds for M • 10 5 M .…”
Section: Observational Predictions For Bh Seeding Modelsmentioning
confidence: 94%
“…Some papers (e.g., Greene & Ho 2006;Mezcua 2017;Martín-Navarro & Mezcua 2018) suggest an alternative scenario for the low-mass regime of the M • − σ relation, predicting a flattening at masses ∼ 10 5 − 10 6 M . Martín-Navarro & Mezcua (2018) explained this putative flattening with a weaker coupling between baryonic cooling and BH feedback, disconnecting the BH from the evolution of the host spheroid.…”
Section: Observational Predictions For Bh Seeding Modelsmentioning
confidence: 99%
“…ing a connection between the star formation and black hole activity , 2018bTerrazas et al 2016Terrazas et al , 2017Martín-Navarro & Mezcua 2018).…”
Section: Black Hole Plus Halo Quenching?mentioning
confidence: 99%